GLP‐1 and peptide YY secretory response after fat load is impaired by insulin resistance, impaired fasting glucose and type 2 diabetes in morbidly obese subjects. (6th May 2013) - Fernández‐García, José C.; Murri, Mora; Coin‐Aragüez, Leticia; Alcaide, Juan; El Bekay, Rajaa; Tinahones, Francisco J.
Summary Objective Both glucagon‐like peptide‐1 (GLP‐1) and peptide YY (PYY) are gut hormones involved in energy homoeostasis. Obesity, insulin resistance and hyperglycaemia are significant confounders when GLP‐1 and PYY secretion is assessed. Thus, we evaluated GLP‐1 and PYY response after fat load in morbidly obese patients with different degrees of insulin resistance and glycemic status. Design We studied 40 morbidly obese subjects (mean age, 40·6 ± 1·3 years; mean BMI, 53·1 ± 1·2 kg/m2) divided into groups according to their glycemic status: normal fasting glucose (NFG) group, impaired fasting glucose (IFG) group and type 2 diabetes mellitus (T2D) group. NFG patients were additionally subclassified, according to the homoeostasis model assessment of insulin resistance (HOMAIR), into a low insulin‐resistance (LIR) group (HOMAIR <3·9) or a high insulin‐resistance (HIR) group (HOMAIR ≥3·9). Measurements Lipid emulsion was administered orally and measurements made at baseline and 180 min postprandially of levels of GLP‐1, PYY, insulin, glucose, free fatty acids, triglycerides and leptin. Results At the 180‐minute postprandial reading, GLP‐1 and PYY had increased in LIR‐NFG subjects (41·84%, P = 0·01; 35·7%, P = 0·05; respectively), whereas no changes were observed in HIR‐NFG, IFG or T2D subjects. Conclusions These results suggest that in morbidly obese subjects, both insulin resistance and abnormal glucose metabolism (IFG or T2D) impair the GLP‐1 and PYY response to fat load. The implications of this attenuated enteroendocrine response should be elucidated by further studies.